PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN ANIMASI BERBANTU APLIKASI KINEMASTER MUATAN IPA METERI SISTEM PENCERNAAN MANUSIA KELAS V SDN 15 KOTO BARU DHARMASRAYA - Rauldatul Husni; Eka Filahanasari; Rahma Surita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
In science learning there is a theme 3 of healthy food, a sub-theme 1 of how the body processes food. Regarding material during the learning process, teachers still use print-based teaching materials such as thematic books and LKS and the lack of use of learning media in teaching and learning activities that can support the learning process. The purpose of this research and development is to develop animated instructional video media in science content, as well as to produce valid, practical, and effective animated video media. This research method is Research and Development (R&D) using the ADDIE model which consists of (1) the analysis stage, (2) the design stage, (3) the development stage, then a validation test is carried out by 3 validator with a result of 94.33% (4) the implementation stage, namely practicality tests carried out by practitioners (teachers) and students with a result of 85.86%. After that, a trial of video media with an effectiveness sheet was carried out to get 82% results obtained from the learning outcomes of students, (5) the evaluation stage (evaluation). Based on the ADDIE procedure used in the research above, it can be concluded that the video animation media that has been developed by researchers is suitable for use, because it meets the minimum valid, practical and effective criteria.